Students' Perspectives on Using Tiktok to Improve Skills in EFL - Oktavena, Nafilla Malika; Maisaroh, Devi Intan; Pradana, Dian Arief (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
This study explores students' perspectives on using TikTok as a tool to enhance their skills in English as a Foreign Language (EFL). With the growing popularity of social media, particularly TikTok, as an educational resource, the research aims to investigate how students perceive the impact of this platform on their language learning. A mixed-method approach was employed, involving surveys and interviews with EFL students to gather qualitative and quantitative data. The findings suggest that TikTok offers a dynamic and engaging way for students to practice listening, speaking, and vocabulary acquisition. Many students reported enjoying the short, creative videos that provide exposure to authentic language use, and they highlighted the platform's interactive features, such as challenges and trends, as motivating factors. However, some students expressed concerns about the quality and accuracy of content, emphasizing the importance of guidance from teachers. The study concludes that while TikTok can be an effective supplementary tool for language learning, its integration into formal education should be carefully monitored. This research contributes to the growing body of literature on the use of social media in education, offering insights into how platforms like TikTok can be leveraged to support EFL learning in the digital age.